Malignant Hypertension Causing a Pulmonary-Renal Syndrome. (17th December 2018) - Yong, Bryan; Power, David A.
Abstract : Background. Pulmonary-renal syndrome is characterised by acute kidney injury, haematuria, and haemoptysis and is a well-recognised presentation of diseases such as ANCA vasculitis that require urgent immunosuppression. Case Presentation. A patient presented with a brief history of haemoptysis, acute renal failure, microscopic haematuria, and severe hypertension. The diagnosis was initially not clear so he was treated with antihypertensives, renal replacement therapy, and immunosuppression. Renal biopsy subsequently showed evidence of malignant hypertension. Autoantibodies were uniformly negative. Conclusions. This case demonstrates that malignant hypertension can present as pulmonary-renal syndrome.